From two kingdoms to one nation : Israel and Judah : studies in division and unification - Gelander, Shamai (Studia Semitica Neerlandica ;, 2011)
How did two separate peoples become one? All the signs are that the creation of a unified Israelite kingdom under King David had failed to erase the differences between the Northern and Southern tribes. This book sets out to highlight these essential differences between Judah and Israel as they appear in various parts of biblical literature. Each of the four chapters of the book focuses on a different aspect of evidence. The first studies the prophet narratives, to elicit the differences between Northern and Southern prophets. The second chapter examines the differences between the Jacob narra.